Analisis Penerapan Strategi Pelayanan Prima dalam Upaya Meningkatkan Jumlah Nasabah pada PT BPRS Carana Kiat Andalas Padang Luar - Safitri, Arnisa; Febrian, Andis (Lembaga Yasin AlSys, 2026)
Excellent service in Islamic financial institutions has received attention in various studies, yet research that specifically discusses the implementation of excellent service strategies in an effort to increase the number of customers at Islamic Rural Banks remains limited. This study aims to analyze the implementation of excellent service strategies in increasing the number of customers at PT BPRS Carana Kiat Andalas Padang Luar. This study used a qualitative approach with a case study design. The research informants consisted of the president director, customer service staff, tellers, financing staff, security officers, and customers selected through purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results show that excellent service strategies at PT BPRS Carana Kiat Andalas Padang Luar are implemented through six main elements, namely ability, attitude, appearance, attention, action, and accountability. Friendly, polite, and professional service contributes positively to customer comfort and satisfaction. However, its implementation still faces several obstacles, such as slow service responses, limited facilities, and the suboptimal use of information technology. This finding contributes to the development of excellent service theory and service quality in Islamic financial institutions. The practical implications of this study emphasize the importance of improving human resource capacity, enhancing service facilities, and optimizing information technology to support customer satisfaction, loyalty, and growth in the number of customers.